Electrical conduction model and equivalent circuit of cementitious composites containing nano additives - Yunyang Wang; Sha Liu; Liqing Zhang; Shengwei Sun; Chenggong Zhao; Yonghui Qin (Case Studies in Construction Materials, 2025)
Electrical conductivity cementitious composites have advantages of superior electrical conductivity, favorable mechanical property, possessing multifunctionality, thus, exhibiting widely prospect in intelligent civil infrastructures. In this paper, the cementitious composites containing the hybrid carbon nano tubes (CNTs) and nano carbon blacks (NCBs) are prepared firstly. And then, the CNTs and NCBs with dosages variation from 0.0 to 5.0 vol% effect on electrical conduction of the composites are systematically investigated. Finally, the electrical conduction model combination with equivalent circuit is proposed to explore the electrical conduction mechanisms in-depth. Results show that the electrical resistivity of the composites is reduced up to three orders of magnitude with increasing concentration of the CNTs and NCBs, and the relationship between electrical conductivity and content of the CNTs and NCBs follows the percolation theory. The electrical conduction features can be precisely explained using the proposed electrical conduction model accompanies with equivalent circuit. The originality of the present study is proposed the electrical conduction model and equivalent circuit of the cementitious composites containing the hybrid CNTs and NCBs. Therefore, the findings of the present research will pave an extensive path for utilization of electrical conductivity cementitious composites in developing multifunctional civil infrastructures.